Hypertensive Disorders of Pregnancy and Cardiovascular Diseases: Current Knowledge and Future Directions - Coutinho, Thais; Lamai, Olabimpe; Nerenberg, Kara (Current treatment options in cardiovascular medicine, 2018)
Purpose of the review Cardiovascular diseases (CVDs) are the principal killers of women. In this review, we summarize data regarding CVD and mortality after hypertensive disorders of pregnancy (HDP), and highlight clinical, research and policy needs to mitigate this risk. Recent findings Robust data indicate that women with HDP have substantially higher risk of future CVD, with a 3.7-fold increase in the risk of chronic hypertension, a 4.2-fold increase in the risk of heart failure, an 81% increase in the risk of stroke, and double the risk of atrial arrhythmias, coronary heart disease, and mortality when compared to women with normotensive pregnancies. Potential explanations include (1) the effect of pregnancy as a “stress test” in women destined to develop CVD, (2) mediation by conventional risk factors, (3) long-term vascular damage sustained during the preeclamptic episode, and (4) preexisting abnormalities in arterial health predisposing women to HDP, and, subsequently, CVD. Summary Women with HDP have significantly increased risk of CVD and mortality. Risk scores including obstetric history are necessary to better estimate a woman’s cardiovascular risk. In addition, comprehensive policies promoting systematic risk assessment and modification after HDP are critically needed to improve health, wellness, and survival of affected women.